Paradox reconsidered: Methane oversaturation in well-oxygenated lake waters - Tang, Kam W.; McGinnis, Daniel F.; Frindte, Katharina; Brüchert, Volker; Grossart, Hans-Peter (Limnology and oceanography, 2014)
The widely reported paradox of methane oversaturation in oxygenated water challenges the prevailing paradigm that microbial methanogenesis only occurs under anoxic conditions. Using a combination of field sampling, incubation experiments, and modeling, we show that the recurring mid-water methane peak in Lake Stechlin, northeast Germany, was not dependent on methane input from the littoral zone or bottom sediment or on the presence of known micro-anoxic zones. The methane peak repeatedly overlapped with oxygen oversaturation in the seasonal thermocline. Incubation experiments and isotope analysis indicated active methane production, which was likely linked to photosynthesis and/or nitrogen fixation within the oxygenated water, whereas lessening of methane oxidation by light allowed accumulation of methane in the oxygen-rich upper layer. Estimated methane efflux from the surface water was up to 5 mmol m−2 d−1. Mid-water methane oversaturation was also observed in nine other lakes that collectively showed a strongly negative gradient of methane concentration within 0–20% dissolved oxygen (DO) in the bottom water, and a positive gradient within ≥ 20% DO in the upper water column. Further investigation into the responsible organisms and biochemical pathways will help improve our understanding of the global methane cycle.